Protective factors against alcohol abuse in college students: spirituality, wisdom, and self-transcendence - Felker, Sydney E., author; Rickard, Kathryn M., advisor; Suinn, Richard M., advisor; Miller, Lisa A., committee member; Le, Thao, committee member (Colorado State University. Libraries, 2011)
Past research consistently suggests that spirituality is a protective factor against substance abuse in adolescents and adults. Many other personality and environmental factors have been shown to predict alcohol abuse and alcohol-related problems, yet much of the variance in alcohol abuse remains unexplained. Alcohol misuse continues to plague college campuses in the United States and recent attempts to reduce problematic drinking have fallen short. In an effort to further understand the factors contributing to students' alcohol abuse, this study examines how spirituality, wisdom, and self-transcendence impact the drinking behaviors of college students. Two groups of students were studied: 1. students who were mandated for psychoeducational and clinical intervention as a result of violating the university alcohol policy; 2. a comparison group of students from the general undergraduate population who had never been sanctioned for alcohol misuse on campus. Alcohol use behaviors were assessed through calculating students' reported typical blood alcohol level and alcohol-related problems. Results showed that wisdom is significantly and negatively related to blood alcohol level and alcohol-related problems for the mandated group but not the comparison group. Self-transcendence was inversely related to blood alcohol level for the control group only and spirituality was not related to alcohol use measures for either group. Participant group membership, gender, and wisdom accounted for a significant amount of variance in blood alcohol level, but only group membership explained variance in alcohol-related problems. Gender analyses were conducted by group, revealing significant differences in how spirituality, wisdom, and self-transcendence relate to alcohol use for men and women. Implications of the findings and suggestions for future research are offered.
Keywords: gender; alcohol; college; self-transcendence; spirituality; wisdom